SOFT SKILLS DEVELOPMENT DESIGN IN TRAINER-Based EDUCATION INSTITUTIONS - Amar, Muhammad Fadali; Yaqin, Muhib Ainul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The development of soft skills is essential because it not only helps students in the academic environment, but also in preparing for future lives. Training-based educational institutions are a container where the development of soft skills can be implemented as an attempt to form a superior generation that also advances Islamic values. In connection with the urgency, the study aims to investigate the design of soft skills development in the internship-based education institute. This research uses a qualitative approach and is carried out at Al-Furqon High School, which is under the umbrella of Pondok Pesantren Al- Furqon, Bondowoso. The findings of this research are that there is a design of development of soft skills that is implemented at al-Fourqon High school, i.e. identification of required soft skills, integration in the curriculum, building groups and organizations, extracurricular activities, cultivation of Islamic values, as well as evaluation and feedback. Besides, there are also some implications of the implementation of soft skill development designs at Al-Furqon High School, namely improved social skills, noble leadership, disciplinary improvement, high participation rates, positive conflict resolution, and improved academic achievement.